(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2014)
This article brings to light the main aspects about the civil and administrative responsability of the companies, which commit unlawful acts against the Public Administration through their legal representatives or controllers, bringing to reflection the improvements and perspectives for the entire integration and efficacy of the Federal Law nº 12.846/2013.